Factors Associated With Mortality in Children Who Successfully Wean From Extracorporeal Membrane Oxygenation*. Issue 9 (September 2018) - Howard, Taylor S.; Kalish, Brian T.; Rajagopal, Satish K.; Williams, Kathryn; Zalieckas, Jill; Thiagarajan, Ravi R.; Alexander, Peta M. A.
Abstract : Objectives: Extracorporeal membrane oxygenation is an established therapy for cardiac and respiratory failure unresponsive to usual care. Extracorporeal membrane oxygenation mortality remains high, with ongoing risk of death even after successful decannulation. We describe occurrence and factors associated with mortality in children weaned from extracorporeal membrane oxygenation. Design: Retrospective cohort study. Setting: Two hundred five extracorporeal membrane oxygenation centers reporting to the Extracorporeal Life Support Organization. Subjects: Eleven thousand ninety-six patients, less than 18 years, supported with extracorporeal membrane oxygenation during 2007–2013, who achieved organ recovery before decannulation. Interventions: None. Measurements and Main Results: Primary outcome was hospital mortality less than or equal to 30 days post extracorporeal membrane oxygenation decannulation. Among 11, 096 patients, indication for extracorporeal membrane oxygenation cannulation was respiratory (6, 206; 56%), cardiac (3, 663; 33%), or cardiac arrest (extracorporeal cardiopulmonary resuscitation, 1, 227; 11%); the majority were supported with venoarterial extracorporeal membrane oxygenation at some stage in their course (8, 576 patients; 77%). Mortality was 13%. Factors associated with mortality included younger age (all < 1 yr categories compared with older, p < 0.05), lower weight among neonates (⩽ 3 vs > 3 kg; p < 0.001), mode of extracorporeal membrane oxygenation support (venoarterial extracorporeal membrane oxygenation compared with venovenous extracorporeal membrane oxygenation, p < 0.001), longer admission to extracorporeal membrane oxygenation cannulation time (≥ 28 vs < 28 hr; p < 0.001), cardiac and extracorporeal cardiopulmonary resuscitation compared with respiratory extracorporeal membrane oxygenation (both p < 0.001), extracorporeal membrane oxygenation duration greater than or equal to 135 hours ( p < 0.001), preextracorporeal membrane oxygenation hypoxemia (PO2 ⩽ 43 vs > 43 mm Hg; p < 0.001), preextracorporeal membrane oxygenation acidemia ( p < 0.001), and extracorporeal membrane oxygenation complications, particularly cerebral or renal (both p < 0.001). Conclusions: Despite extracorporeal membrane oxygenation decannulation for organ recovery, 13% of patients die in hospital. Mortality is associated with patient factors, preextracorporeal membrane oxygenation illness severity, and extracorporeal membrane oxygenation management. Evidence-based strategies to optimize readiness for extracorporeal membrane oxygenation decannulation and postextracorporeal membrane oxygenation decannulation care are needed.